Long-term effects of organic inputs on yield and soil fertility in the rice-wheat rotation - Yadvinder-Singh; Bijay-Singh; Ladha, J.K.; Khind, C.S.; Gupta, R.K.; Meelu, O.P.; Pasuquin, E. (Wiley, 2004)
The sustainability of the rice (Oryza sativaL.)–wheat (Triticum aestivumL.) rotation is important to Asia's food security. Intensive cropping with no return of crop residues and other organic inputs result in the loss of soil organic matter (SOM) and nutrient supply, and is assumed to be nonsustainable. We evaluated seven treatments comprised of various combinations of green manure (GM;Sesbania cannabinaL.); wheat straw (WS), farmyard manure (FYM), and urea on yields and yield trends; P and K balance; and soil fertility in a rice–wheat experiment (1988–2000) on a loamy sand in Punjab, India. Rice yields were comparable with GM + urea, WS + GM + urea, and urea alone, but yields were reduced when FYM was supplemented with N. Except during 1 yr, integrated use of FYM and GM produced equal or higher rice yields than other GM based treatments. Wheat straw incorporation reduced average rice yields by 7% compared with WS removal. After 5 yr of continuous application, FYM and WS were at par in increasing rice yields. Organic materials applied to rice had no residual effect on wheat yields except FYM, which increased yield by about 6% compared with urea alone. Rice yield declined by 0.02 to 0.13 Mg ha−1yr−1but wheat yields remained unchanged. Soil C increased with the application of WS and FYM. Potassium balance was highly negative. Although the causes of yield decline are unknown, inadequate K applications and changes in the climatic parameters are possible reasons.